Dostoevsky and the novel - Holquist, Michael, 1935-2016 (Princeton legacy library., 1977)
What place do Dostoevsky's works occupy in the history of the novel? To answer this question, Michael Holquist focuses on the formal aspects of Dostoevskian narrative. The author argues that the novel is a genre that constantly seeks its own identity: we still do not know what it is, since the uniqueness of its members defines the class to which it belongs. This anomaly explains the central role of the novel for Russians, perplexed as they were in the nineteenth century by idiosyncrasies that hindered development of a coherent national identity. Michael Holquist shows that the generic imp.